Adolescent growth and its relation to menarche, dental and somatic maturation - Kaczmarek, Maria (Anthropological Review, 2002)
Relationships between growth in height during adolescence and menarche, somatic, and dental maturation were analyzed on longitudinal data for 181 boys and 176 girls from the Poznań Growth Study. It was found that the correlation pattern between variables shifts during the spurt indicating the following regularities: The younger and smaller the boys and girls were at the onset of the spurt, and the lower the height velocity at that time, the longer their spurt was likely to last, and the adolescent height increment was larger. Neither the timing of the spurt, nor the spurt duration or height gain had and influence on the final height. The maturation of the dentition was weekly, or no significantly, correlated with growth in height. The age at menarche revealed significant correlations with all characteristics of the growth spurt except for adolescent increment and adult height.